Analisis Pemahaman Prinsip-Prinsip Pengelolaan Koperasi Syari’ah pada Pengurus dan Anggota Koperasi Mesjid di Kota Medan - Rivai Iqrok Tanjung; Zuhrinal M. Nawawi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
The purpose of this study is to find out and analyze how the community's efforts in understanding sharia cooperatives in daily life are in accordance with Islamic sharia through trainings carried out by the Medan City MSME cooperative service. In this case using research with qualitative methods where this method is to understand the relationship between public finances and its relationship with Islam which regulates it where financial problems do not stop and continue for an unknown time as well as human needs in wanting to fulfill their every need in a state of financial resources. limited. For this reason, it is important to understand the importance of cooperatives in meeting needs and how to get them. As well as the importance of understanding that cooperatives are not only conventionally based, but also sharia based cooperatives in an effort to apply financial principles in accordance with Islamic sharia. Keywords: Finance, Islam, Sharia, Cooperatives